Recent Advances in pH- or/and Photo-Responsive Nanovehicles - Yuseon Shin; Patihul Husni; Kioh Kang; Dayoon Lee; Sehwa Lee; Eunseong Lee; Yuseok Youn; Kyungtaek Oh (Pharmaceutics, 2021)
The combination of nanotechnology and chemotherapy has resulted in more effective drug design via the development of nanomaterial-based drug delivery systems (DDSs) for tumor targeting. Stimulus-responsive DDSs in response to internal or external signals can offer precisely controlled delivery of preloaded therapeutics. Among the various DDSs, the photo-triggered system improves the efficacy and safety of treatment through spatiotemporal manipulation of light. Additionally, pH-induced delivery is one of the most widely studied strategies for targeting the acidic micro-environment of solid tumors. Accordingly, in this review, we discuss representative strategies for designing DDSs using light as an exogenous signal or pH as an endogenous trigger.